2020
DOI: 10.1021/acs.iecr.0c02478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Application of a Perforated Anode in an Aluminum Electrolysis Cell on the Gas–Liquid Two-Phase Flow and Bubble Distribution Characteristics

Abstract: In contrast to the original form of the anode, the perforated anode is a new kind of anode that can significantly reduce the bubble thickness while maintaining a stable electrolysis process. The bubble movement was simulated within physical and mathematical models of the flow field in the anode–cathode distance (ACD) area, in which the electrolyte solidification zone in the anode perforations was treated creatively as a porous medium. The flow field distribution and the bubble layer thickness in the ACD area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…have been discussed in detail. 43,44 It has been successfully applied to the development of methods for optimizing the operation of current sources, 45 preventing anodizing effects during electrolysis, 46 and forming metal nanoparticles on the surface of the oxide to obtain new materials and other aspects. 47 However, the common factors affecting the diffusion at solid-liquid interface and the formation of surface wetting contact angle, are not sufficiently studied.…”
Section: Metal-based Molten Salt Batterymentioning
confidence: 99%
“…have been discussed in detail. 43,44 It has been successfully applied to the development of methods for optimizing the operation of current sources, 45 preventing anodizing effects during electrolysis, 46 and forming metal nanoparticles on the surface of the oxide to obtain new materials and other aspects. 47 However, the common factors affecting the diffusion at solid-liquid interface and the formation of surface wetting contact angle, are not sufficiently studied.…”
Section: Metal-based Molten Salt Batterymentioning
confidence: 99%
“…Research has shown that bubbles adhering to the electrode surface will affect the actual current density, causing areas HCO − covered by bubbles to exhibit electrochemical inertia 13 , which also affects the distribution of current density on the electrode surface 14 . The movement of bubbles in the water can change the ow eld in the water 15,16 , which in turn affects the growth of bubbles 17,18 . Higher current density promotes bubble growth, but the movement of bubbles can also cause changes in resistance 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,21] Many research types focus on the original electrolytic cell structure optimization to accelerate the escape of bubbles or stabilize the flow field. [22,23] The influence of structural parameters of the electrolytic cell on the thermal field is studied to reduce energy consumption. [24] The heat balance of electrolytic cells is the basis of the numerical simulation of the physical field.…”
Section: Introductionmentioning
confidence: 99%